Determinants of antiretroviral therapy adherence in northern Tanzania: a comprehensive picture from the patient perspective - Lyimo Ramsey A; de Bruin Marijn; van den Boogaard Jossy; Hospers Harm J; van der Ven André; Mushi Declare (BMC, 2012)
Abstract Background To design effective, tailored interventions to support antiretroviral therapy (ART) adherence, a thorough understanding of the barriers and facilitators of ART adherence is required. Factors at the individual and interpersonal level, ART treatment characteristics and health care factors have been proposed as important adherence determinants. Methods To identify the most relevant determinants of adherence in northern Tanzania, in-depth interviews were carried out with 61 treatment-experienced patients from four different clinics. The interviews were ad-verbatim transcribed and recurrent themes were coded. Results Coding results showed that the majority of patients had basic understanding of adherence, but also revealed misconceptions about taking medication after alcohol use. Adherence motivating beliefs were the perception of improved health and the desire to live like others, as well as the desire to be a good parent. A de-motivating belief was that stopping ART after being prayed for was an act of faith. Facilitators of adherence were support from friends and family, and assistance of home based care (HBC) providers. Important barriers to ART adherence were the use of alcohol, unavailability of food, stigma and disclosure concerns, and the clinics dispensing too few pills. Strategies recommended by the patients to improve adherence included better Care and Treatment Centre (CTC) services, recruitment of patients to become Home Based Care ( HBC) providers, and addressing the problem of stigma through education. Conclusion This study underscores the importance of designing tailored, patient-centered adherence interventions to address challenges at the patient, family, community and health care level.